Q. 375.0( 2 Votes )

If X and

Answer :


We have
       n(X) = 17
       n(Y) = 23
       n(X ∪ Y) = 38
By using the formula, 
          n(X ∪ Y) = n(X) + n(Y) - n(X ∩Y)
We have 38 = 17 + 23 - n(X ∩ Y)
  ...  n(X ∩ Y) = 17 + 23 - 38
  ...  n(X ∩ Y) = 40 - 38
  ...  n(X ∩ Y) = 2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses